2022
DOI: 10.1002/ceat.202200443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2‐Pyrrolidone Protic Ionic Liquids on Removal of Pyridine from Fossil Fuel Model Mixtures

Abstract: To reduce emission of nitrogen oxides (NOx) mainly produced from the combustion of nitrogen compounds (NCs) in fossil fuels, it is necessary to decrease the NCs content in fossil fuels. 2‐Pyrrolidone‐based protic ionic liquids (PrILs) with three different anions were synthesized by a one‐step method. The three PrILs were used as extractants to extract pyridine from the model mixtures. The extraction efficiency (EE) was considered to evaluate the extraction performance of the PrILs. The interactions between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The denitrification efficiency was enhanced 375 ) and membranes for the selective separation of N-containing compounds from model fuel comprising pyridine, quinoline, isoquinoline, and heptane. 379 The permeation rates for different SILMs were predominantly governed by the polarity of the permeating species.…”
Section: Extractive Denitrification (Edn) Using Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The denitrification efficiency was enhanced 375 ) and membranes for the selective separation of N-containing compounds from model fuel comprising pyridine, quinoline, isoquinoline, and heptane. 379 The permeation rates for different SILMs were predominantly governed by the polarity of the permeating species.…”
Section: Extractive Denitrification (Edn) Using Ilsmentioning
confidence: 99%
“…The denitrification efficiency was enhanced by designing three 2-pyrrolidone-based functionalized ILs combining different acidic anions [HSO 4 ] − , [H 2 PO 4 ] − , and [NO 3 ] − ([Pyr]­[HSO 4 ], [Pyr] [H 2 PO 4 ] , and [Pyr]­[NO 3 ]) for pyridine extraction from a model fuel comprising n -hexane and toluene with an extraction efficiency of 99.53%, 99.36%, and 95.02% respectively (optimized extraction conditions: the mass ratio of solvent to fuel = 1:5, initial content for N-containing compound = 5 wt %, and extraction time = 30 min). The mechanism of denitrification based on QC calculations showed that the magnitude of intermolecular interaction between functionalized ILs and pyridine was in the order of [Pyr]­[HSO 4 ] > [Pyr]­[H 2 PO 4 ] > [Pyr]­[NO 3 ], consistent with the experimental EDN activity.…”
Section: Heterocyclic Compound Extraction Using Ilsmentioning
confidence: 99%